Multiculturalismo no Bom Retiro (SP): o caso do col??gio de Santa In??s - Mello, Isabella Delcorso Cury de (2019)
This paper presents the case of the Santa Ines School in the neighborhood of Bom Retiro in the city of S??o Paulo. The neighborhood has a multicultural, ethnic and religious feature, as immigrants from various parts of the world (from jews to koreans) settled in the area. In this scenario, the school was responsible for welcoming this diversity, even if it was a catholic school. In order to understand how this reception was given, Salesian nuns who had a significant passage in the institution were interviewed. Thus, a research on oral history was carried out to find out how the interviews would be carried out, a deepening of Salesian pedagogy, to know the proposal of the school, and a study on multiculturalism, to learn about the intercultural reality of the students. Studying the interculture together with the Salesian pedagogy proved to be effective for understanding the education offered by the traditional College and how the multicultural differences in the city of S??o Paulo are treated.